A new nonlinear stochastic volatility model with regime switching stochastic mean reversion and its applications to option pricing. (February 2023) - He, Xin-Jiang; Lin, Sha
Abstract: We establish a new nonlinear stochastic volatility model by modeling the volatility long-run mean with a particular stochastic process, whose parameters can jump between different regimes according to a Markov chain. Introducing the regime switching factor is consistent with the empirical evidence of the economic cycle and nonlinear volatility mean-reversion observed from market data. A closed-form solution that can be used to value European options has been successfully obtained based on the characteristic function approach, followed by some numerical examples comparing the models with and without regime switching. Highlights: We propose a new nonlinear three-factor stochastic volatility model. We capture economic cycles and nonlinear volatility mean-reversion. We present a closed-form solution for European option pricing.